Tiktok as a Learning Tool for Elementary School Students - Amaluisa Rendón, Paulina Magally; Espinosa-Pinos C.A.; Núñez-Torres M.G. (My University, 2023)
The large number of users of the social network Tiktok worldwide and the studies that demonstrate the advantages of its use in relation to its educational capacity encourage us to seek new ways of teaching. The present study was conducted at the Indoamerica Educational University in the city of Ambato-Ecuador during the 2021–2022 school year, comparing the motivation of students of General Basic Education: specifically, Basic Middle (Sublevel 3): fifth, sixth and seventh grade corresponding to boys and girls of 9, 10 and 11 years old respectively, and the use of Tiktok as a learning tool demonstrated in their academic performance. Group A has used Tiktok as a tool for the development of academic activities, while group B has not used it. A quantitative methodology was used with a descriptive-inferential procedure and a qualitative analysis through interviews with educators. A pre-test and a post-test were carried out to demonstrate the children's motivation at the end of the school year. It is confirmed that the children who used Tiktok as a learning tool consider themselves more motivated and show a greater dedication to the proposed subject matter than children who do not use it, which is evidenced in their academic record. On the other hand, the teachers interviewed expressed heterogeneous opinions. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Electrical measurements; IoT; M5Stack; remote monitoring; web server